Characterization and immunomodulatory activities of polysaccharides from Spirogyra neglecta (Hassall) Kützing - Utoomporn Surayot (2018)
© 2015 Japan Society for Bioscience, Biotechnology, and Agrochemistry. Sulfated polysaccharides (SP) isolated from freshwater green algae, Spirogyra neglecta (Hassall) Kützing, and fractionated SPs were examined to investigate their molecular characteristics and immunomodulatory activity. The crude and fractionated SPs (F1, F2, and F3) consisted mostly of carbohydrates (68.5-85.3%), uronic acids (3.2- 4.9%), and sulfates (2.2-12.2%) with various amounts of proteins (2.6-17.1%). D-galactose (23.5- 27.3%), D-glucose (11.5-24.8%), L-fucose (19.0- 26.7%), and L-rhamnose (16.4-18.3%) were the major monosaccharide units of these SPs with different levels of L-arabinose (3.0-9.4%), D-xylose (4.6-9.8%), and D-mannose (0.4-2.3%). The SPs contained two sub-fractions with molecular weights (Mw) ranging from 164 × 103to 1460 × 103g/mol. The crude and fractionated SPs strongly stimulated murine macrophages, producing considerable amounts of nitric oxide and various cytokines via up-regulation of their mRNA expression by activation of nuclear factor-kappa B and mitogen-activated protein kinases pathways. The main backbone of the most immunoenhancing SP was (1→3)-L-Fucopyranoside, (1→4,6)-D-Glucopyranoside, and (1→4)-D-Galactopyranoside.